Digital platform for scaling climate information services in Mali - Diallo, Aboubacar; Bengaly, Oumar; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This study analysed the digital platform established by the AICCRA project to disseminate climate information services in Mali. In total, 233,000 farmers of which 38% are women had access to CIS through the digital platforms. On average, farmers having access to CIS through the digital platform had an increase in their yield by 705 kg/ha, income by 345,288 XOF/ha (575 USD/ha) and food consumption score by 2. When the cumulative benefits of the digital platform were evaluated, access to the digital platform increased rice production by 164,265 ton and farmers’ income by 134 million USD.